Epigenetics in Human Obesity and Type 2 Diabetes - Ling, Charlotte; Rönn, Tina (Cell metabolism, 2019)
Epigenetic mechanisms control gene activity and the development of an organism. The epigenome includes DNA methylation, histone modifications, and RNA-mediated processes, and disruption of this balance may cause several pathologies and contribute to obesity and type 2 diabetes (T2D). This Review summarizes epigenetic signatures obtained from human tissues of relevance for metabolism—i.e., adipose tissue, skeletal muscle, pancreatic islets, liver, and blood—in relation to obesity and T2D. Although this research field is still young, these comprehensive data support not only a role for epigenetics in disease development, but also epigenetic alterations as a response to disease. Genetic predisposition, as well as aging, contribute to epigenetic variability, and several environmental factors, including exercise and diet, further interact with the human epigenome. The reversible nature of epigenetic modifications holds promise for future therapeutic strategies in obesity and T2D. Epigenetic factors are suggested to contribute to metabolic dysfunctions. In this Review, Ling and Rönn summarize evidence for altered DNA methylation, both as a cause and a consequence of human obesity and type 2 diabetes. As epigenetic alterations are dynamic in nature, they may also provide targets for drug development.